2017
DOI: 10.1111/cogs.12554
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Effects of Input Frequency and Morphophonological Complexity on Children's Acquisition of Verb Inflection: An Elicited Production Study of Japanese

Abstract: This study aims to disentangle the often‐confounded effects of input frequency and morphophonological complexity in the acquisition of inflection, by focusing on simple and complex verb forms in Japanese. Study 1 tested 28 children aged 3;3–4;3 on stative (complex) and simple past forms, and Study 2 tested 30 children aged 3;5–5;3 on completive (complex) and simple past forms, with both studies using a production priming paradigm. Mixed effects models for children's responses were built to test the prediction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…This pattern of emergence would seem to count against the idea that complex forms emerge later than simple forms (e.g. Bassano, 2000; Iwatate, 1981; Takanashi, 2009), and is consistent with the idea that complex endings can be acquired early provided they are sufficiently frequent in the input (Tatsumi et al, 2018).…”
Section: Study 1: Descriptive and Correlational Analysis Using Type-bsupporting
confidence: 54%
“…This pattern of emergence would seem to count against the idea that complex forms emerge later than simple forms (e.g. Bassano, 2000; Iwatate, 1981; Takanashi, 2009), and is consistent with the idea that complex endings can be acquired early provided they are sufficiently frequent in the input (Tatsumi et al, 2018).…”
Section: Study 1: Descriptive and Correlational Analysis Using Type-bsupporting
confidence: 54%
“…They found that verbs that are more consistently conjugated in a certain common form compared to other possible forms, such as siru “come to know” with the imperfective aspect morpheme -te-i-(ru) , were produced exclusively in the common form early in the learning trajectory, while this preferential bias was not observed in verbs that do not have a common form. In a recent study on Japanese L1 acquisition, Tatsumi et al (2018) investigated 3–5-year-olds’ productive use of different forms (simple past tense vs. completive past tense) of verbs in a primed elicited production paradigm, in which the children described actions in line-drawings after hearing the experimenter describing the previous drawing using a verb in the uncommon completive past-tense form. It was found that children’s choice between simple and completive form for each verb reflected the relative frequency of the two forms in corpus data.…”
Section: Discussionmentioning
confidence: 99%
“…The relative frequency of different morphological forms of the same word have been found to predict usage, language change, accuracy, and error patterns in language processing and acquisition ( Bybee, 1985 ; Hay, 2001 ; Matthews and Theakston, 2006 ; Sugaya and Shirai, 2009 ; Tatsumi et al, 2018 ). Hay’s (2001) study of relative frequency in derivational morphology, which follows proposals on the structure of paradigms (groups of inflectionally related words with a common lexical stem) in Bybee (1985 , Chapter 3), demonstrates that the more frequent member of a paradigm is more accessible and less compositional.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that these frequency effects at the levels of both target and competing forms are not found only in very complex systems, where children have no ‘choice’ but to store a multiplicity of individual exemplars. They are found also for systems that are virtually exceptionless, such as English 3sg -s marking (Räsänen, Ambridge, & Pine, 2014) and Japanese past/non-past marking (Tatsumi, Ambridge, & Pine, 2018), where there is no ‘need’ to store individual ready-inflected forms (e.g. fits, plays, runs, walks ) at all, since all could in principle be generated from the bare/non-finite form (e.g.…”
Section: Morphologically Inflected Wordsmentioning
confidence: 99%